Dynamic of Economic Motives of Indonesia’s Migrant Workers’ Remittances - As'ad, As'ad; Ekananda, Mahjus (Jurnal Ekonomi & Studi Pembangunan, 2024)
This study investigates empirical evidence regarding the economic motives underlying remittances from Indonesian migrant workers. Economic motives play a crucial role in remittances behavior, as they determine the amount of money workers send to their families in their home country based on various economic indicators. Although extensive research exists on this topic, there remains no definitive consensus about the economic motivations behind migrant workers’ remittances. This research provides additional perspectives on these economic motives, particularly in the Indonesian context. Using a fixed effects model to overcome individual effect bias, this study finds evidence of investment motives in Indonesian’s migrant workers’ remittances. However, these findings are contingent upon Indonesia’s economic condition. The motivations tend to be individualistic during periods of economic stability and altruistic during economic uncertainty. The knowledge gained from understanding these economic motives can help related parties formulate strategies for economic activities involving migrant workers' remittances in accordance with Indonesia's economic conditions.